THE ROLE OF INVESTIGATORS OF THE CYBER DIRECTORATE OF THE REGIONAL POLICE NORTH SUMATERA IN HANDLING CRIMINAL ACTS IN THE FIELD OF BANKING THROUGH CYBER INTERMEDIARIES - Pasaribu, Hendri Goklas; Syahrin, Alvi; Robert, Robert (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
In line with the development of the times and the increasing development that is also inseparable from all aspects related to human life. Related to developments in people's lives for all existing problems, which are increasingly easy to solve or vice versa, there are also a small number of people who experience difficulties related to facing and meeting their needs. This has resulted in the rapid development of technology that is developing in society. Development at this level of technology will also have an impact on the impacts that occur in almost all aspects of human life, and will also change people's behavior, and human civilization, on the other hand, related developments in the field of technology have resulted in life in the world becoming limitless. Against the increasingly rapid technological advances, of course, it will have an impact in terms of positive or negative aspects. However, in line with the development of the times, the use of information technology has changed both in terms of people's behavior and those related to human civilization in general. With the advancement of technology, banking also follows technological developments, by creating applications that aim to provide convenience to customers so that in carrying out transactions in the form of checking and payments can be done using mobile banking and internet banking only by using a smartphone without having to come to the bank or to an ATM machine.